Consumption, wealth, and income inequality: A tale of tails - Alexandre Gaillard; Christian Hellwig; Philipp Wangner; Nicolas Werquin (Federal Reserve Bank of Chicago, 2023)
We provide evidence that the distributions of consumption, labor income, wealth, and capital income exhibit asymptotic power-law behavior with a strict ranking of upper tail inequality, in that order, from the least to the most unequal. We show analytically and quantitatively that the canonical heterogeneous-agent model cannot replicate the proper ranking and magnitudes of these four tails simultaneously. Mechanisms addressing the wealth concentration puzzle in these models through return heterogeneity lead to a mirror consumption concentration puzzle. We match the cross-sectional data on these four Pareto tails by positing a combination of non-homothetic, wealth-dependent preferences and scale-dependent returns to capital. We underscore the importance of these results by showing that all four dimensions of top inequality jointly determine the long-run elasticity that governs the revenue-maximizing capital tax rate.
Keywords: 330; Spending; Wealth; Consumption; Saving; Income Distribution; Modeling; Taxation and Subsidies; Fiscal Policies; Firm Behavior